Contributions of the Circular Economy to the Leather Life Cycle: A Theoretical Review and Integrative Framework Proposal - De Almeida, Ilton Marchi [UNESP]; Jugend, Daniel [UNESP]; Deus, Rafael Mattos; De Souza, Fernando Bernardi [UNESP] (My University, 2021)
Due to its economic and environmental importance, the leather production chain has received much attention from researchers and intergovernmental organisations in recent years. However, the academic literature has not yet debated how the circular economy (CE) can contribute to the life cycle of leather. This work advances this theme through a systematic review and content analysis to identify and analyse the CE principles and initiatives that contribute to a reduction in the potential environmental impacts of the leather life cycle. Among its main contributions, this work discusses the environmental impacts of the leather production life cycle, presents potential relationships between the leather production phases and CE, and proposes an integrative framework for CE and the leather life cycle.